Archival strategies and social order during the Spanish Civil War and the Francoist dictatorship - Pastor Núñez, Guillermo; Alonso Rodríguez, Henar; Rial Quintela, María del Carmen (Hispania Nova, 2021)
This study presents a reflection on the ability of archives to reveal the nature of the social order that generates them, especially in political situations acted on by dynamics of conflict and resistance. As paradigms of this ability of the archives, three samples of the Spanish Civil War and the Francoist dictatorship have been selected: first, three archives of the non-rebeled social order; secondly, the archive of the Servicio de Información y Policía Militar, introducing the less explored series; finally, the sumarísimos, due to its condition of documentation of required reference in researches on Francoist repression.
Keywords: archives; spanish civil war; exile; social order; repression; francoism